Case report: Fatal insulin overdose in a dog with type 1 diabetes mellitus—characteristics and successful management - Park, Jun-Hyeong; An, Ju-Hyun; Kim, Se-Hoon; Choi, Han-Sol; Kim, Tae-Hyeon; Oh, Ye-In; Seo, Kyoung-Won; Youn, Hwa-Young (Frontiers in Veterinary Science, 2023)
Administering more than 10 times the therapeutic dose of insulin is extremely rare in diabetic dogs and is life threatening with hypoglycemia and seizures if not accompanied by appropriate treatment.A 15-year-old, castrated male miniature poodle dog managed for diabetes presented with depression, disorientation, ataxia, and cluster seizures. The dog had been administered 11.1 U/kg of neutral protamine hegadorn (NPH) insulin (10 times the prescribed dose) 3 h before the onset of symptoms.Blood analysis revealed hypoglycemia, with a circulating glucose level of < 50 mg/dL. To treat the hypoglycemia-induced seizures, dextrose was repeatedly administered intravenously. Repeated generalized seizures were treated with anticonvulsants and intermittent mannitol. Since refractory hypoglycemia persisted 24 h after the insulin overdose, it was decided to proceed with glucagon treatment (15-30 ng/kg/min titrated to the blood glucose level after a loading dose of 50 ng/kg intravenous bolus infusion). After 37 h of glucagon treatment, blood glucose levels stabilized. After entering a hyperglycemic state, NPH insulin was administered to manage insulin-dependent diabetes mellitus. This is the first case documented of successful treatment with glucagon, anticonvulsants and intermittent mannitol for refractory hypoglycemia and seizure caused by fatal insulin overdose. Thus, it has great clinical value in veterinary medicine.